Studi Hadis - Hadis Terhadap Puasa di Hari Jum’at - Desi Mita Septi; Ilham Mustafa (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2025)
This study is motivated by the study of prophetic traditions on fasting on Friday, there is also this study means to pursue how the traditions of the prophet will fast on Friday and also the explanation of the traditions of the prophet on fasting on Friday. Because again many believers do not understand if fasting 1 day specifically on Friday is prohibited and allowed if accompanied by 1 day before and 1 day after the same as contained in the traditions of the Prophet. In this study, the observer used a type of library research by accumulating data directly from the library or from romances related to the essay's subject by direct methods. In contrast, the type of study used in this study is a qualitative study by observing the procedures for understanding the conversations of the apostle by considering various thoughts or by general methods, which is a science that discusses the methodological principles (methods and procedures) of understanding the conversations of the apostle as a result of which the apostle's conversations can be understood by suitable methods. The explanation of the Prophetic traditions on fasting on Friday uses a contextual approach. Based on the results of the study, it can be concluded that the majority of Believers avoid fasting on Friday. Not only that, in the conversation of the apostle the Apostle also ordered his people to fast on Friday accompanied by 1 day before or 1 day after which is found in the narration of Sahih Bukhari: meaning “None of you should fast on Friday but accompanied by one day at a time before or after it”.